2018
DOI: 10.1590/1809-4430-eng.agric.v38n5p768-775/2018
|View full text |Cite
|
Sign up to set email alerts
|

BIOHYDROGEN PRODUCTION IN AnSBBR IN FED-BATCH FROM STARCH EFFLUENT: INFLUENCE OF ORGANIC LOAD

Abstract: The hydrogen is a fuel with a high energy density. Studies have sought to verify the potential of different residues and configurations of reactors in the production of biohydrogen. This study evaluated the influence of the organic loading rate on the production of biohydrogen from cassava starch wastewater (CSW) in anaerobic sequencing batch biofilm reactors (AnSBBR) operated in a fed-batch. In the tests, the organic loading rates of 9.0; 13.5 and 18.0 gCT L-1 d-1 were used, at cycle times (CT) of 4; 4 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…According to Na Ayudthaya et al (2018), Mañunga et al (2019), and Colin et al (2006), it is common to find large amounts of organic acids and the presence of lactic acid‐producing bacteria in the composition of cassava wastewater. Studies using a pretreated mixed microorganism culture have reported the presence of lactic acid in the fermentation; however, the authors did not optimize its production (Baghchehsaraee, 2009; Baghchehsaraee et al, 2008; Tonello et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Na Ayudthaya et al (2018), Mañunga et al (2019), and Colin et al (2006), it is common to find large amounts of organic acids and the presence of lactic acid‐producing bacteria in the composition of cassava wastewater. Studies using a pretreated mixed microorganism culture have reported the presence of lactic acid in the fermentation; however, the authors did not optimize its production (Baghchehsaraee, 2009; Baghchehsaraee et al, 2008; Tonello et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Sludge was obtained using a full‐scale three‐chamber anaerobic baffled reactor to treat cattle manure and dairy barn wastewater, and then submitted to thermal treatment and three successive inoculations in Reinforced Clostridial Medium (RCM), as an evolutionary adaptation, to obtain an enriched culture of acidogenic microorganisms adapted to fermentative processes. The thermal treatment has the objective of inhibiting the growth of methanogenic bacteria, based on the methodologies described by Baghchehsaraee (2009), and some studies have used this strategy to produce lactic acid (Baghchehsaraee, 2009; Baghchehsaraee et al, 2008; Tonello et al, 2018). Firstly, the sludge was sieved to remove coarse solids.…”
Section: Methodsmentioning
confidence: 99%
“…Cassava starch wastewater (CSW) is rich in easily degradable carbohydrates and nutrients, 6 making this effluent to be widely employed as a substrate in studies that address the production of fermentative hydrogen in continuous 7,8 and discontinuous processes, 9,10 with suspended 11,12 or attached cell growth 13‐15 . Usually, these systems are subjected to organic loading rate (OLR) levels varying between 10 and 80 g L −1 d −1 8,16 and hydraulic retention time (HRT) between 2 and 24 hours 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In its applications, a wide range of products of economic and environmental value (e.g. methane, hydrogen, carboxylic acids) have been recovered from anaerobic treatment under different reactor configurations and operating conditions, 7,20‐22 varying key parameters for the process (temperature, pH, alkalinity) 23‐26 under distinct hydraulic retention times (HRT) 27‐29 …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In its applications, a wide range of products of economic and environmental value (e.g. methane, hydrogen, carboxylic acids) have been recovered from anaerobic treatment under different reactor configurations and operating conditions, 7,[20][21][22] varying key parameters for the process (temperature, pH, alkalinity) [23][24][25][26] under distinct hydraulic retention times (HRT). [27][28][29] Despite the substantial interest in carrying out further research on effluent digestion, only a few studies have performed a systematic analysis of the contributions from scientific publications on the subject.…”
Section: Introductionmentioning
confidence: 99%